Leadership styles and organizational commitment: a study at Majlis Daerah Ketereh Perbandaran Islam (MDKPI) / Syameri Ahmad - Ahmad, Syameri (2015)
This research investigates the relationship between leadership styles which are Transformational Leadership and Transactional Leadership with organizational commitment at Majlis Daerah Ketereh Perbandaran Islam (MDKPI). The literature provides the discussion on two variables of leadership such as Transformational Leadership and Transactional Leadership. Information gathered from 100 respondents. Transformational Leadership and Transactional Leadership were identified as the independent variables while organizational commitment as the dependent variable. Data obtained from each of the research instruments was then statistically analyzed. In addition, based on the result from linear regression analysis, it was concluded that there is a significant influence between transformational leadership and organizational commitment. Meanwhile, there is also significant value between Transactional Leadership and organizational commitment. Pearson Correlation analysis showed that there is a strong positive relationship between both leadership which are transformational leadership and transactional leadership with organizational commitment. The finding indicated that, in order to enhance organizational commitment, the company should train their leader on how to become transformational leader and transactional leader. Interpretation of results, implication and future research are discussed.